Pengaruh Literasi Keuangan, Gaya Hidup, Uang Saku, dan Gender terhadap Pengelolaan Keuangan pada Mahasiswa Kota Banyuwangi - Sevia Aylula Putry; Abadi Sanosra; Jekti Rahayu (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
College students, as the younger generation in higher education, face significant challenges in achieving financial independence. Low levels of financial literacy, a consumptive lifestyle, dependence on parental allowances, and gender influence are important factors that deserve further study in shaping students' financial management behavior. This situation is increasingly relevant amidst the increasing needs of students to meet educational costs, lifestyle, and social demands, which are often not matched by adequate financial management skills. This study aims to analyze the influence of financial literacy, lifestyle, allowances, and gender on the financial management of college students in Banyuwangi City. The research method used was quantitative, with a survey approach using a questionnaire with 50 student respondents from various study programs. The data obtained were analyzed using multiple linear regression to examine the relationship and influence of independent variables on student financial management. The results showed that financial literacy and lifestyle significantly and positively influenced student financial management. This means that the greater students' understanding of financial concepts and the wiser they are in managing their lifestyles, the better their financial management skills. In contrast, the variables of pocket money and gender did not show a significant effect, indicating that neither the amount of pocket money nor gender differences directly influence students' financial behavior. These findings indicate that improving financial literacy through formal and non-formal education, as well as fostering a frugal lifestyle, are key to developing students' ability to manage their finances wisely. This research offers practical implications for higher education institutions and policymakers to design more systematic financial education programs to enable students to achieve sustainable financial independence.